Differences In Service Quality Of Government Hospital And Private Hospital In Purbalingga Regency Using HCAHPS Method - Mustika Ratnaningsih Purbowati; Ira Citra Ningrom (Universitas Muhammadiyah Purwokerto, 2023)
The quality of hospital services can be assessed from various perspectives, one of which is the patient's perspective. Good service quality will foster patient confidence in the hospital and will come back and even recommend to others. Good service quality will also create a good degree of public health. To determine the difference in the quality of service of government hospitals and private hospitals in Purbalingga district. This type of research is quantitative, with an observational analytic design and a cross-sectional approach. The number of samples is 100 respondents, consisting of 50 inpatients in government hospitals and 50 inpatients in private hospitals. The research instrument used the HCAHPS (Hospital Consumers Assessment Providers and Systems) questionnaire. The sampling technique used non-probability sampling with purposive sampling and analyzed using the Mann Whitney comparative test. Mann Whitney comparative test of service quality of government hospitals and private hospitals in Purbalinga Regency showed p-value on the doctor's communication component 1.00 (> 0.05), nurse communication 0.325 (> 0.05), hospital environment 0.205 (> 0.05), experience hospitalized 0.204 (>0.05), discharge information 0.155(>0.05), overall hospital 1.00 (>0.05), self-care comprehension after hospitalization 0.977 (>0.05). There is no difference in the service quality of government hospitals and private hospitals in Purbalingga Regency